The Rosia Montana Gold Deposit, Rosia Montana, Transylvania, Romania - C S. Szentesy; K Howie (The Australasian Institute of Mining and Metallurgy, 2002)
The Rosia Montana gold deposit is located within the æGolden QuadrilateralÆ area in the Apuseni Mountains of Transylvania, Romania. The deposit is situated approximately 85 kilometres north of the regional centre of Deva, within the province of Alba, at elevations of up to 1100 metres above sea level. The Rosia Montana deposit contains a current resource of 344.07 million tonnes at an average grade of 1.3 grams per tonne (g/t) gold (Au) and 6.0 g/t silver (Ag) for a total (measured, indicated and inferred) contained resource of 14.29 million ounces of gold and 67.00 million ounces of silver. The resource was calculated using a 0.6g/t Au cut-off, a 10 x 10 x 10 metre block size and multiple indicator kriging. The low sulfidation style epithermal mineralisation at Rosia Montana is hosted within Tertiary age dacite intrusions and related vent breccias. Mineralisation is generally disseminated and associated with silica, adularia, illite, pyrite and carbonate alteration of host rocks, with minor late carbonate-base metal veins. Precipitation of precious metals is generally considered to have occurred as a result of over-pressurization, boiling and subsequent brecciation. The dacite intrusions are hosted in Cretaceous shallow marine and deltaic shales and slates, which overlie older Paleozoic sedimentary and metamorphic rocks within uplifted sections of oceanic sea floor.